Katalog kompetenc in regije v Evropski uniji - Bačlija Brajnik, Irena (Teorija in praksa, 2006)
Region is a space between states and local level of authority and administration. It is a space where issues of public interest that are to extensive and complex for the state level, are solved and addressed. Regions and their role became important just with the creation and extension of the European Union since the majority of the so called European policies are carried out at the regional level. In addition the harmonic regional development stands as one of the basic strategic aims of the EU. However, since the regional forms differ between the countries according to historical, geographical and cultural characteristics, there is a question, howto grasp, equally evaluate and burden them with the unified regional politics. In addition, there is no individual arrangement to be an example: a wide span makes simple ranking impossible. Taking into account increasingly laud demands of stronger European regions (Germany, Spain) for gaining greater competence in co-decision making on public policies on supranational level to be carried out exactly on the regional level, there is a question if the introduction of Catalogue of competence to more clearly arrange the relations between the EU, member states and regions, is reasonable. The authors attempt to introduce the question that was completely overlooked in a hot debate in Slovenia regarding the number of regions: what are the tasks and the roles of Slovenian regions and comparatively other regions in the Europe. They also introduce the opinions of Slovenian decision makers at the local level.
Keywords: European Union; Evropska unija; Local self-government; Lokalna samouprava; local government; Regions; Regije; Regionalism; Regionalizem; Competences; Slovenia; Pristojnosti; Slovenija